Navigating Compliance: Regulatory Technology's Role in Anti-Money Laundering in Indonesia Banking - Wibowo, Ilham Gema; Setijaningsih, Herlin Tundjung (Dinasti Publisher, 2024)
The financial sector system is unlawfully used for money laundering, which causes massive losses for the state and country. An essential component of successfully combating money laundering is regulatory technology (RegTech). This study aims to investigate the impact of implementing Electronic Know Your Customer (e-KYC), transaction monitoring (TM), cost and time efficiencies (CTE), regulatory compliance (RC), and technology information infrastructure (ITI), in money laundering preventing (MLP) in the banking sector in Indonesia. A quantitative method is used to explore the interplay of variables. The research sample consists of 50 owners of BRI Link agents. Data analysis is conducted using a linear regression model. The study's findings underscore the significant influence of TM, CTE, RC, and ITI on the effectiveness of PML, with CTE emerging as the most influential driver. Despite a moderately positive correlation among these factors, the e-KYC provided by regulatory technology (RegTech) does not exert a substantial impact on MLP. The implications of this research suggest that the adoption of RegTech, positively contributes to MLP efforts in banking institutions, highlighting the importance of utilizing technology and regulations to enhance Anti Money Laundry (AML) measures.